(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
So, for example, in the production of cheese, fat-soluble vitamins are excreted into the serum, but the concentration of calcium does not change. In terms of digestibility and amino acid composition, milk proteins are considered very valuable. If the nutritional value of an egg is taken as 1, then for milk this indicator will be 0.9. There is less cysteine and methionine in milk, but there are a lot of them in whey.